(untitled) (Bioscience Journal, 2025)
This research aimed to evaluate the impact of different treatment modalities, involving flower cluster thinning and plant growth regulators, on the fruit characteristics, antioxidant properties, and mineral composition of triploid ‘Cheonghyang’ grapes. The lengths of the inflorescences were adjusted to 5 cm or 6 cm immediately before full bloom. Subsequently, various plant growth regulator treatments were administered at full bloom to thinned flowers, including GA₃ at 100 ppm, GA₃ at 100 ppm combined with thidiazuron at 2.5 ppm or 5.0 ppm, and GA₃ at 100 ppm combined with CPPU at 2.5 ppm or 5.0 ppm. The treatment combining GA₃ (100 ppm) and CPPU (5.0 ppm) with 6 cm flower cluster thinning exhibited the highest cluster weight and berry firmness. These values surpass those obtained from the commonly used GA₃ (100 ppm) treatment in Korean vineyards. Although this treatment regimen showed a relative reduction in total soluble sugar content compared to the other treatments, it still resulted in berries with exceptional marketability. Furthermore, this treatment regimen displayed a superior accumulative effect on DPPH radical scavenging activity and mineral content, indicating a substantial contribution to functional enhancement. In summary, the combined application of flower cluster thinning and plant growth regulators presents a practical approach for augmenting the marketability of triploid ‘Cheonghyang’ grapes.